Knowledge, Attitudes and Practices in Hygiene and Food Handling of Workers in the Restaurants of Miraflores and Lurigancho-Chosica, 2017 - Torres Ramírez, Ruth Madelen (2018)
Objective: Determine the relationship of knowledge, attitudes and practices on hygiene and food handling of workers in the restaurants of Miraflores and Lurigancho-Chosica. Methodology: descriptive and correlational type. The sample consisted of 125 manipulators from Miraflores and 125 from Lurigancho-Chosica; The questionnaire on knowledge, attitudes and practices on hygiene and food handling was used. Results: The results showed that in Miraflores and Lurigancho Chosica 70.4% and 59.2% had high knowledge about hygiene and food handling, similarly, in both districts, very positive attitudes about hygiene and food handling were found in 94.4% and 93.6% respectively. In Miraflores, 97.6% of handlers present a high level of practices, while in Lurigancho Chosica the proportion is lower with 54.4%. Conclusion: it was observed that Miraflores handlers have a higher level of knowledge and practices on hygiene and food handling that the district of Lurigancho Chosica, despite this result was found a very positive attitude about hygiene and food handling in both districts. On the other hand, knowledge and attitudes are correlated to both districts in a significant way.